2008
DOI: 10.1108/17511060810919443
|View full text |Cite
|
Sign up to set email alerts
|

The gap between wine expert ratings and consumer preferences

Abstract: Purpose -Expert wine awards are commonly used by consumers to reduce complexity in wine choice but little is known about expert vs non-expert perceptions of sensory wine quality. This paper aims to examine if expert ratings are suitable quality indicators for consumers and whether there are certain groups of consumers that find expert awards more useful than others. Design/methodology/approach -The paper compares German consumer ratings obtained in a sensory laboratory with German Agricultural Society's qualit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(34 citation statements)
references
References 16 publications
0
34
0
Order By: Relevance
“…An attempt to explain the differences observed in effect sizes between these two studies by conducting a comparison of the two different consumer groups is not possible, as limited wine behaviour data and wine involvement and knowledge information were described by Lattey et al (2010). Schiefer and Fischer (2008) collected socio-demographic and wine consumption and behavioural data not dissimilar to ours. They then compared these German wine consumers' quality ratings with expert quality awards for German Riesling wines and found that wine consumers with wine experience of between 4.5 and 24.5 years better replicated expert ratings (Schiefer & Fischer, 2008).…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…An attempt to explain the differences observed in effect sizes between these two studies by conducting a comparison of the two different consumer groups is not possible, as limited wine behaviour data and wine involvement and knowledge information were described by Lattey et al (2010). Schiefer and Fischer (2008) collected socio-demographic and wine consumption and behavioural data not dissimilar to ours. They then compared these German wine consumers' quality ratings with expert quality awards for German Riesling wines and found that wine consumers with wine experience of between 4.5 and 24.5 years better replicated expert ratings (Schiefer & Fischer, 2008).…”
Section: Discussionmentioning
confidence: 92%
“…Schiefer and Fischer (2008) collected socio-demographic and wine consumption and behavioural data not dissimilar to ours. They then compared these German wine consumers' quality ratings with expert quality awards for German Riesling wines and found that wine consumers with wine experience of between 4.5 and 24.5 years better replicated expert ratings (Schiefer & Fischer, 2008). Notably, our consumer cohort averaged 22.6 years wine experience.…”
Section: Discussionmentioning
confidence: 97%
“…This large amount of missing data poses severe estimation problems (Kamakura, Basuroy, & Boatwright, 2006). Second, there are several sensory studies which found a disconnect between consumers' blind product preferences and expert evaluations (Delgado & Guinard, 2011;Goldstein et al, 2008;Schiefer & Fischer, 2008), suggesting that critics' ratings are only very limitedly informative of consumers' sensory preferences. Last, there is a potential model specification endogeneity issue for those critics who do not assess wines blindly, as price was found to exert a very strong subliminal effect on human product evaluation (Plassmann, O'Doherty, Shiv, & Rangel, 2008).…”
Section: Variables Not Included In the Modelmentioning
confidence: 98%
“…One reason a wine's region is important to consumers is because wine can be classified as credence good, as wine lacks easily comparable attributes (Schiefer and Fischer, 2008). While some products are easy to evaluate before purchase and easy to evaluate after purchase and consumption (i.e.…”
Section: Origin Effects and Product Ethnicity: The Case Of Old World mentioning
confidence: 99%